An Exploration of Multidisciplinary Team Care With Digital Technology for Complicated Cranio-Maxillofacial Bone Defects and Fractures. Issue 7 (October 2020) - Liu, Yutong; Wang, Yiqun; He, Xifan; Li, Fangjie; Zhang, Sheng; Wang, Kai; Chen, Lin; Wu, Hanjiang
Abstract : Objective: Early treatment of fractures of the cranio-maxillofacial complex (CMFC) is challenging and likely to result in craniofacial deformity. Multidisciplinary team (MDT) care has developed very rapidly and has recently been accepted in cancer treatment. Therefore, the authors explored the application of MDT care with digital technology in CMFC fractures. Study Design: A 29-year-old man presented for treatment of CMFC fractures and bone defects. An MDT of oral surgeons, ophthalmic surgeons, neurological surgeons, and other experts was convened. After CT scan and three-dimensional reconstruction, the authors performed personalized surgery that included 9 specialists over an 8-hour period. Results: The operation was successful and all fractures achieved clinical stability. At 1-month follow-up, appropriate appearance and functional recovery had been achieved. Conclusion: In this study, MDT care with digital technology was very effective and had low associated costs. The involvement of more disciplines in MDT care may result in fewer complications.